Employees’ perceptions toward on-site childcare centres to working parents / Farah Fatini Zainal Abidin and Raja Nur Syakirin Raja Ibrahim - Zainal Abidin, Farah Fatini; Raja Ibrahim, Raja Nur Syakirin (2018)
This chapter is divided into several sections. It starts with Section 1.1 that touched on the basis of the study. Section 1.2 is regarding the background of the study. It is being continued with Section 1.3 that is discussing research objectives. In addition, Section 1.4 is concerned with the heart of the research which is research problems. This section is the most important part of the research study. Besides, Section 1.5 is regarding the significance of study while Section 1.6 is on the scope of research. In Section 1.7, focusing on research questions. On the other hand, Section 1.8 is highlighting the hypotheses while Section 1.9 focused on the definition of terms. This research is relating to the employees’ perceptions toward on-site childcare to working parents. The research is being conducted in the higher institution, Universiti Teknologi MARA that involves two campuses which are UiTM Tapah, Perak and UiTM Raub, Pahang.